2007
DOI: 10.1080/15298860600980185
|View full text |Cite
|
Sign up to set email alerts
|

Beyond nature and nurture: The influence of lay gender theories on self-stereotyping

Abstract: 2008) Beyond nature and nurture: The influence of lay gender theories on self-stereotyping, Self and Identity, 7:1, 34-53,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 39 publications
2
101
0
4
Order By: Relevance
“…It is possible that teachers who endorse biologically based differences in learning as a rationale for single-sex schooling may (consciously or unconsciously) also reinforce gender stereotypes in the classroom, a possibility that should be tested in future research. Furthermore, students who endorse rationales focusing on gender differences in interests may be inclined to limit their own interests and activities to stereotype-consistent domains (or "self-stereotype"; Coleman and Hong 2008). To the extent that stakeholders within single-sex schools believe in brain-based learning differences, they may create environments that foster greater knowledge of and compliance with cultural gender stereotypes.…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that teachers who endorse biologically based differences in learning as a rationale for single-sex schooling may (consciously or unconsciously) also reinforce gender stereotypes in the classroom, a possibility that should be tested in future research. Furthermore, students who endorse rationales focusing on gender differences in interests may be inclined to limit their own interests and activities to stereotype-consistent domains (or "self-stereotype"; Coleman and Hong 2008). To the extent that stakeholders within single-sex schools believe in brain-based learning differences, they may create environments that foster greater knowledge of and compliance with cultural gender stereotypes.…”
Section: Discussionmentioning
confidence: 98%
“…However, there is evidence that accounts of gender that emphasise biological factors leave us more inclined to agree with gender stereotypes, to selfstereotype ourselves, and for our performance to fall in line with those stereotypes (e.g., [2,7,8]). Moreover, other research from the social psychological literature has shown that presenting cognitive or emotional tasks in ways that make them seem diagnostic of gender tends to set up a self-fulfilling prophecy (e.g., [3,14,15,[21][22][23][24]).…”
Section: Meet Sarahmentioning
confidence: 99%
“…In this way, essentialism may also be seen as a guiding set of beliefs that motivates an individual to adhere to gender norms. For instance, seeing gender differences as largely biologically driven is associated with one's own endorsement of traditional gendered traits; furthermore, experimentally promoting an essentialist view of gender causes a corresponding strengthening of how gender-typical one views oneself (Coleman and Hong 2008). As well, being told that gender differences in math performance are largely genetically driven (vs. caused by cultural and social experiences) has been found to exacerbate stereotype threat effects in women's math performance (Dar-Nimrod and Heine 2006).…”
Section: Social Essentialism and Social Cognitionmentioning
confidence: 96%